Inovasi Manajemen Pendidikan di Madrasah Tsanawiyan Negeri Model Samarinda - Mukhamad Ilyasin (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2019)
The spirit of innovation in Education management in the MTs Negeri Model Samarinda that has been built bringing the school having advantages among other schools in Samarinda. One of the efforts made is to make innovations on managerial aspects. The efforts to prepare short and medium term plans in the context of a strategic plan involving internal human resources that represent the needs of the education community in Samarinda and consider the strengths and opportunities they have resulted in making the school obtain an A accreditation that reflects the quality of well education. This study aims to determine management innovation in MTs Negeri Model Samarinda. This research is a field work research that aims to find the innovations in management education in MTs Negeri Model Samarinda including the aspects of planning, implementation and evaluation. Sources of data in this study are the school’s headmaster, curriculum filed, facilities and infrastructure filed and several teachers. In conducting the data collection, the writer uses three kinds of techniques, namely observation, interviews and documentation. Furthermore, the author analyzes using the Milles and Huberman interactive analysis model, with data reduction flow, data preparation and conclusion drawing. Based on the findings of the study, the writer concluded as follows: Education management innovation in MTs Negeri Model Samarinda is carried out with reference to three stages: First, Innovation at the planning stage which includes the process of goals, problem identification, support and inhibitors, alternative solutions to problems, alternatives decision making, and evaluation. Second, innovation at the implementation stage which includes the process of socialization, polling, and dissemination. Third, innovation at the evaluation stage which includes the process of identifying problems, scaling priorities, problem analysis, alternative solutions, and following-up plans.